2017
DOI: 10.1097/mib.0000000000001236
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Fatty Acid Metabolism Modify the Association Between Dietary n3

Abstract: Introduction High intake of dietary n-3 polyunsaturated fatty acids (PUFA) is associated with a decreased risk of ulcerative colitis (UC) and Crohn's disease (CD). However, results have been heterogeneous suggesting that genetic variations in PUFA metabolism may modify this risk. Methods We conducted a case-control study nested within two prospective cohorts, the Nurses' Health Study (NHS) and NHS II. Among women providing blood (n=62,437) or buccal cells (n=59,543) for genotyping, we confirmed new diagnoses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…The cluster is built about a 283 kb region on chromosome 11 that contains the DAGLA, MYRF, TMEM258, RP11-467L20, FADS1, FADS2, FADS3 , and BEST1 genes (Fig 2b; S3 Table). Consistent with this observation, genetic variations in the FADS1 – FADS3 region have previously been associated with alterations in the synthesis of PUFAs 32 , inflammatory bowel diseases 33 , cholesterol levels and BMI 34 , coronary artery disease and type 2 diabetes 35 , and colorectal cancer 36 .…”
Section: Resultssupporting
confidence: 61%
“…The cluster is built about a 283 kb region on chromosome 11 that contains the DAGLA, MYRF, TMEM258, RP11-467L20, FADS1, FADS2, FADS3 , and BEST1 genes (Fig 2b; S3 Table). Consistent with this observation, genetic variations in the FADS1 – FADS3 region have previously been associated with alterations in the synthesis of PUFAs 32 , inflammatory bowel diseases 33 , cholesterol levels and BMI 34 , coronary artery disease and type 2 diabetes 35 , and colorectal cancer 36 .…”
Section: Resultssupporting
confidence: 61%
“…In contrast, the diet–gene interaction model has also been a controversial topic. A recent nested case–control study reported that no association was found between the ratio of n-6 to n-3 PUFAs and the risk of Crohn's disease under consideration of SNPs at CYP4F3 and FADS2 loci [ 36 ].…”
Section: Epidemiology Of Diet and Crohn's Diseasementioning
confidence: 99%
“…A case-control study has suggested that the association between dietary n3: n6 PUFA intake and risk of UC may be modified variants at CYP4F3. High n3: n6 PUFA intake was associated with reduced risk of UC in individuals with GG/AG genotype at a single nucleotide polymorphism in CYP4F3 [114] . Barnes EL et al [115] reported that increased intake of multiple fatty acids was associated with increasing odds of relapse and specific fatty acids, i.e., myristic acid (commonly found in palm oil, coconut oil, and dairy fats) that may associate with an increasing risk of flare.…”
Section: (4) Sarcopeniamentioning
confidence: 94%